Cycling Tourism on the Danube Cycle Route in Serbia: Residents’ Perspective - Pavluković, Vanja; Kovačić, Sanja; Stankov , Uglješa (Eastern European Countryside, 2024)
Cycling tourism is a rapidly developing type of tourism in Europe and it is recognised in the tourism strategic documents of the Republic of Serbia as one of the key tourist products that should be developed specifically in the Danube region. This paper aimed to examine residents’ perceptions towards cycling tourism on the Danube cycle route in Serbia using the modified Tourism Impact Attitude Scale (TIAS). In addition, a multiple regression model was used to test the effects of the independent variables on residents’ perceptions towards cycling tourism development. The research findings indicate that residents have a favourable attitude towards cycling tourism, which is in the initial phase of development in the study area, and that the independent variables are predictors of residents’ perceptions. Implications for tourism development and planning are discussed and future research opportunities provided.